1971
DOI: 10.1002/jmor.1051350303
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the antenna and its sensory cone in larvae of Aedes aegypti (L.)

Abstract: The fine structure of the antenna and of the antennal sensory cone, the largest of the eight antennal sensilla, of fourth instar larvae of the mosquito Aedes aegypti are described and discussed. The antennal integument supports and encloses only sensillar elements. The antennal sensory cone seems to be a chemoreceptor of a modified composite basiconic type. It is innervated by about 12 neurons grouped into six units. Each neuronal unit has a trichogen and tormogen cell, but no neurilemma or other accessory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Not surprisingly, the number and morphology of larval antennal terminal structures were consistent among individuals and throughout larval instars, as well as similar to those described for Ae. aegypti (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, the number and morphology of larval antennal terminal structures were consistent among individuals and throughout larval instars, as well as similar to those described for Ae. aegypti (9).…”
Section: Resultsmentioning
confidence: 99%
“…Vacuoles were observed near the base of the cone, similar to those found in Ae. aegypti, that may function in lipid-soluble odor detection (9). The An.…”
Section: Resultsmentioning
confidence: 99%
“…6 B and D, which is published as supporting information on the PNAS web site). Both organs house terminal sensilla in mosquitoes that are thought to be chemosensory in function on the basis of their fine structures (27,36). In the case of the maxillary palpus, labeling was clear in a small number of cell bodies and in projections into the sensillar cone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 6) is in agreement with Vosshall et al (14), who observed that DOr83b was expressed in D. melanogaster larvae. The distal end of the larval antenna and maxillary palpus of mosquitoes contain several innervated, sensory-type structures that potentially function in both olfaction and gustation (27,36). Specific expression of the AgOR7 protein in these tissues is consistent with their having a chemosensory function, although it remains unclear whether that role may be olfactory, gustatory, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Zacharuk 1970), the effects of the molting process on infection by microbial pathogens, and the structural nature of the cuticular apparatus of insect sense organs and its role in sensillar function (e.g. Scott and Zacharuk 1971 ;Zacharuk 1971b;Zacharuk et al 1971).…”
Section: Introductionmentioning
confidence: 99%